(untitled) (Research, Society and Development, 2025)
Diabetes Mellitus (DM) is a Noncommunicable Chronic Disease characterized by hyperglycemia and it is primarily classified into type 1, type 2, gestational, and prediabetes. The two main types are associated with a deficiency in the production or action of insulin, the hormone responsible for regulating glucose metabolism. This study aimed to evaluate the level of knowledge among health science students regarding DM, its symptoms, risk factors, and related health behaviors. A quantitative survey was conducted with 429 undergraduate students enrolled at Unipar – Cascavel Campus, Paraná, using an online questionnaire administered via Google Forms. Among the participants, 33.8% were unable to define DM, and 52.9% did not recognize its symptoms. Only 4.9% reported having a diabetes-related condition. A concerning correlation emerged between limited knowledge and the adoption of unhealthy lifestyle habits, while 52% of respondents reported a family history of diabetes. Furthermore, 15 students reported the use of oral antidiabetic medications, and 11 reported the use of exogenous insulin. Some participants acknowledged the use of hypoglycemic agents without a formal medical diagnosis, indicating a self-medication rate of 70%. Among female students, insulin use without medical supervision was often associated with attempts at weight management and improved self-esteem, revealing the impact of aesthetic pressures. These findings reveal that the lack of knowledge about DM among health students is alarming and underscores the need for educational strategies that integrate clinical training with awareness of health, medication safety, and body image issues.